La enfermedad y la escritura: Atisbos a la poética de José Watanabe - Rangel, Asunción (Acta Hispanica, 2017)
The topic of the illness reveals at various points in Peruvian-Japanese poetry José Watanabe. Born in 1945 in Laredo, Peru, he died at the age of 62, suffering from throat cancer. It is not strange to find allusions to the degenerative process of the body – derived from the disease – and to the cure in, for example, “Krankenhaus” (hospital, in German), a section of the book El huso de la palabra (1989). In his poetry about disease, Watanabe involves, on the one hand, knowledge derived from medicine and, in addition, knowledge that is outside the frame of writing: advice, family or community stories, what lives and arises –to put it with one of his verses– “en la honda boca de los mayors”. The notion of disease that is poetically devised, links medical knowledge and those that come from the family. The idea of the disease must be incorporated into the way of living it. The sick body to which Watanabe refers is one who feels, perceives and experiences the ailment as a way of living, but also as a way of dying: the agony. His poetry is a way of living dying and dying in living, within the framework of disease that is nothing other than agony. This comparison is significant if we take into account that the process of writing and reading are seen as the life of poetry (in its writing, in its reading) that goes, as it progresses verse by verse, irremediably to death. At the end of reading the poem, it dies; while reading, agonizes. This allows you to venture a path of reading that splices writing, body, disease, life and death.